2011
DOI: 10.1261/rna.2628611
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity and diversity of tRNA anticodon determinants of substrate recognition by eukaryotic A37 isopentenyltransferases

Abstract: The N 6 -(isopentenyl)adenosine (i 6 A) modification of some tRNAs at position A37 is found in all kingdoms and facilitates codonspecific mRNA decoding, but occurs in different subsets of tRNAs in different species. Here we examine yeasts' tRNA isopentenyltransferases (i.e., dimethylallyltransferase, DMATase, members of the D 2 -isopentenylpyrophosphate transferase, IPPT superfamily) encoded by tit1 + in Schizosaccharomyces pombe and MOD5 in Saccharomyces cerevisiae, whose homologs are Escherichia coli miaA, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
139
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(154 citation statements)
references
References 37 publications
12
139
0
Order By: Relevance
“…The PHA6 northern blot assay is based on a DNA probe complementary to the anticodon loop which hybridizes better in the absence of i6A37 and a probe complementary to a different region of the same tRNA as a quantitative internal control. The procedure can be used to calibrate and measure differences in i6A37 modification (Lamichhane et al 2011(Lamichhane et al , 2013a(Lamichhane et al , b, 2016Yarham et al 2014).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…The PHA6 northern blot assay is based on a DNA probe complementary to the anticodon loop which hybridizes better in the absence of i6A37 and a probe complementary to a different region of the same tRNA as a quantitative internal control. The procedure can be used to calibrate and measure differences in i6A37 modification (Lamichhane et al 2011(Lamichhane et al , 2013a(Lamichhane et al , b, 2016Yarham et al 2014).…”
Section: The State Of the Trna Population In The Cellmentioning
confidence: 99%
“…Our in silico analysis and the interspecies complementation tests suggest that Drosophila Tcs3 is implicated in t 6 A synthesis. This modification was detected using an adaptation of a hybridization method used to detect the presence of N 6 -isopentenyl-adenosine (i 6 A), another modification found at position 37 of specific tRNAs (43). Briefly, when the threonylcarbamoyl moiety is present in position Ala-37, it impairs Watson-Crick pairing between the tRNA and the specific DNA FIGURE 2.…”
Section: Drosophila Tcs3 Is Required For Organismal and Cell Auton-mentioning
confidence: 99%
“…A tRNA modification in bacteria, yeast, and animals is isopentenyl-N 6 -A37 (i6A37). In eukaryotes, i6A37 is found on cytosolic and mitochondrial tRNAs (cy-and mt-tRNAs) (Dihanich et al 1987;Lakowski and Hekimi 1996), intriguingly, on different subsets of tRNAs in different species (Lamichhane et al 2011(Lamichhane et al , 2013a for review, see Maraia and Iben 2014). In bacteria, i6A37 is hypermodified to 2-methylthio-N 6 -isopentenyl-A37 (ms2i6A37).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast lacking IPTase grow normally in standard media (Laten et al 1978;Janner et al 1980;Laten 1984;Dihanich et al 1987). Schizosaccharomyces pombe has five i6A37-cy-tRNAs, comprised of three cy- (Chan and Lowe 2009;Lamichhane et al 2011). An assay in S. pombe dependent on decoding of a Tyr codon in the active center of β-galactosidase revealed that loss of i6A37 decreased cy-tRNA Tyr specific activity by approximately threefold (Lamichhane et al 2013a).…”
Section: Introductionmentioning
confidence: 99%